2005
DOI: 10.1051/0004-6361:20042535
|View full text |Cite
|
Sign up to set email alerts
|

The $\mathsf{\Sigma}$ – Drelation for supernova remnants in nearby galaxies

Abstract: Abstract. This paper examines relations between the radio surface brightness Σ and the diameter D (also known as Σ − D relations) for a sample of extragalactic supernova remnants (SNRs) as constructed from a combination of published data and data from our own surveys. Our sample of extragalactic SNRs is the largest ever devised for the purpose of analyzing Σ − D relations. The main results of this paper may be summarized as follows: (i) the empirical relations for SNRs in 10 of the 11 nearby galaxies studied h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 70 publications
(90 reference statements)
8
43
0
Order By: Relevance
“…For Galactic samples, Malmquist bias 4 may be the most severe effect; this is similar to the situation for Galactic SNR samples (Urošević et al 2005).…”
Section: The Empirical σ−D Relation For Pnesupporting
confidence: 65%
See 1 more Smart Citation
“…For Galactic samples, Malmquist bias 4 may be the most severe effect; this is similar to the situation for Galactic SNR samples (Urošević et al 2005).…”
Section: The Empirical σ−D Relation For Pnesupporting
confidence: 65%
“…1. Malmquist bias tends to increase the slope of the Σ − D relation for SNRs (Urošević et al 2005). Similar implications should be valid for PNe as well.…”
Section: The Empirical σ−D Relation For Pnesupporting
confidence: 60%
“…For Galactic SNRs, Green (2005) highlighted the selection effects: (1) in the surface brightness, with a completeness limit of about 10 −20 W m −2 Hz −1 sr −1 , while SNRs below this limit are predominantly in regions where the Galactic background is low; (2) in the angular size, so that young but distant SNRs may be missed. For SNRs in other galaxies, Urošević et al (2005) also showed that there may be a selection effect in the integrated flux (valid for unresolved or mildly resolved SNRs), with the effect of leading to an observed slope shallower than the intrinsic one.…”
Section: Introductionmentioning
confidence: 89%
“…Various authors (e.g., Clark & Caswell 1976;Milne 1979;Caswell & Lerche 1979;Case & Bhattacharya 1998;Urošević et al 2005) have investigated this correlation. Originally applied as a tool for estimating SNR distances, it has been found to be unreliable for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation